The Relationship of Cortisol Levels and Sleep Quality in Acute Ischemic Stroke Patients: A Literature Review - Lisda Amalia (Jurnal Neuroanestesi Indonesia)
Hormonal factors are one of several elements that contribute to the process by which patients with acute ischemic stroke experience poor sleep quality. The hypothalamic-pituitary-adrenal (HPA) axis is responsible for producing the hormone cortisol. When the hypothalamus is activated, it releases vasopressin and Corticotropin Releasing Hormone (CRH), both of which influence Adrenocorticotropic Hormone (ACTH). This hormone triggers release of cortisol and other glucocorticoids by the adrenal glands. The HPA axis becomes engaged during an acute disease. Cortisol levels will rise as a result of HPA axis activation. Specifically, injury to the frontal or medial temporal lobes of the brain, as well as inflammation, or a lack of regulation of the HPA axis, can lead to this medical condition. Cortisol levels might remain elevated for up to seven days following the start of a stroke. An increase in cortisol levels is connected to an highly risk of stroke severity, length of hospital stay, and mortality in stroke patients. It is also an early warning sign of deteriorating sleep quality in patients with acute ischemic stroke.